Analysis of the Influence of Economic Growth Income Inequality and Poverty Reduction in North Sumatra - Isnaini Harahap; M Ridwan; Ihsaniyah Limbong (Budapest International Research and Critics University, 2022)
This study aims to analyze the effect of economic growth and income inequality on poverty alleviation in North Sumatra, and determine whether the level of influence of economic growth is pro-poor or anti-poor. The method used is panel data analysis of 33 regencies/cities in North Sumatra in the 2016-2020 period, the results of the study show that economic growth and income inequality in North Sumatra have a negative effect on poverty. Meanwhile, seen from the net elasticity of poverty, income inequality becomes an obstacle or reduces the effectiveness of economic growth in alleviating poverty. Economic growth in North Sumatra during 2016-2020 is pro poverty (pro poor) of 0.338.